Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1086/512228
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Structure and Geometry of Winds from Luminous Blue Variables via Fitting the Continuum Energy Distributions

Abstract: By combining the UV spectra from IUE with photometric data in the optical band, we present a quantitative study on the continuum energy distributions of LBVs to determine the structure and geometry of LBV winds. It is shown that the shape of continuum energy distributions around the Balmer jump is sensitive to the velocity law of LBV winds. A simple, spherically symmetric wind model including free-bound and free-free radiation is constructed to compute the continuum energy distributions of LBVs. By matching th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 76 publications
(114 reference statements)
1
8
1
Order By: Relevance
“…All these parameters, as well as wind clumping and line blanketing, affect the shape of the continuum, and the assumed values by Guo & Li (2007) are significantly different than the values derived in this paper. Our detailed fits to the line profiles require a much slower velocity law (β = 3) for the wind of AG Car than that determined by Guo & Li (2007). 7.3.…”
Section: Comparison With Previous Workcontrasting
confidence: 69%
“…All these parameters, as well as wind clumping and line blanketing, affect the shape of the continuum, and the assumed values by Guo & Li (2007) are significantly different than the values derived in this paper. Our detailed fits to the line profiles require a much slower velocity law (β = 3) for the wind of AG Car than that determined by Guo & Li (2007). 7.3.…”
Section: Comparison With Previous Workcontrasting
confidence: 69%
“…Guo et al (2005) suggested that this may be due to a decrease of neutral hydrogen because of collisions in the dense wind, due to extra emission from the recombination of hydrogen, or due to the more extended atmospheres in which the velocity field changes with the radius and the lines of the Lyman series could be spread out. Guo & Li (2007) showed that the continuum energy distribution around the Balmer jump is sensitive to the wind velocity law. Second, the observed spectral energy distribution of LBVs in outburst may be a combination of two sources (the central star and the envelope).…”
Section: Discussionmentioning
confidence: 99%
“…In some objects in certain phases, however, β attains a significantly higher value, up to β∼ 4 (Najarro, Hillier & Stahl 1997; Groh et al 2009). In general, LBV stars have low β≲ 1 during optical minima, but the velocity law changes during eruptions (Guo & Li 2007). We now consider the effect of the variable β parameter on model spectrum.…”
Section: The Modelmentioning
confidence: 99%